Epidemiology of injuries in National Collegiate Athletic Association men's baseball: 2014-2015 through 2018-2019 - Boltz, A. J.; Powell, J. R.; Robison, H. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association has supported men's baseball championships since 1947. Since its inception, the number of participating teams and athletes has considerably expanded. Background: Frequently conducting injury surveillance of collegiate baseball athletes is essential for identifying developing temporal patterns. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics; injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 3.16 per 1000 athlete-exposures. The preseason injury rate was significantly higher than the regular season injury rate. The most commonly injured body parts were shoulder (16.1%), arm or elbow (16%), and hand or wrist (13.9%). The most reported specific injury was hamstring tear (7.9%). Conclusions: The findings of this study aligned with previous studies—most injuries were due to noncontact and overuse mechanisms, less than one-half of injuries were related to upper extremity body parts, and one-third of all injuries were reported among pitchers.